(untitled) (Research, Society and Development, 2025)
Vaccination is one of the most effective public health strategies for preventing vaccine-preventable diseases. This article aims to present a study on protection and care through a vaccination campaign against hepatitis B, yellow fever, and MMR (measles, mumps, rubella) for military police officers of the North CPA (Military Police Command), in the city of Manaus, Amazonas State. It is a descriptive experience report with a qualitative approach, limited to the military police officer population, encompassing individuals of different age groups. The results achieved by the lecture during the vaccination campaign against Hepatitis B, Yellow Fever, and MMR for Military Police Officers showed broad participation, demonstrating interest and understanding of the importance of immunization as a strategy for health protection and maintaining operational activities. The experience highlighted the fundamental role of nursing in the execution and coordination of preventive immunization campaigns and for collective protection.